"What do interlocks do" revisited – a bibliometric analysis. Issue 4 (30th November 2020) - Smith, Matthew; Sarabi, Yasaman
Abstract : Purpose: It has been over 20 years since the landmark publication of Mizruchi (1996) and his examination of "what do interlocks do?". Since then, the nature of interlocks and subsequent research on the subject has evolved. This paper aims to revisit the literature on interlocking directorates through a quantitative bibliometric analysis. Design/methodology/approach: This study undertakes a bibliometric analysis of literature citing the Mizruchi (1996) to examine the state of research following up on "what do interlocks do". This study examines 718 publications using keyword and co-word analysis, along with a thematic analysis to revisit the research that has followed Mizruchi's topic of what do interlocks do. Findings: This study finds that the topics of the corporate elite, capitalist economy and corporate governance have remained prominent themes in the field. Research areas that are emerging in the field of interlocking directorates include gender diversity, globalisation and advancing theoretical frameworks. Originality/value: This paper provides a quantitative bibliometric analysis to revisit the extant literature on "what do interlocks do", examining a high number of articles to identify areas which could be developed to advance research in the field.